تحسين أداء الاتصالات الضوئية المترابطة باستخدام الهزازات الليزرية - مخائيل سليم مخول (Tishreen University, 2019)
يتضمن بحثنا دراسةً لتأثير المضخمات والتحكم بالاستقطاب على أداء اتصالات الألياف البصرية المترابطة، ويقدم تعريفاً بمخطط صندوقي لنظام اتصال ضوئي مترابط جديد. من خلال الدراسة الرياضية، والنمذجة لنظام الاتصال الليزري المترابط، تبين أن: • نظم اتصالات الألياف البصرية المترابطة تقدم حساسية مستقبلات، وانتقائية أفضل من نظم الكشف المباشر. • القدرة الضوئية الساقطة على الكاشف الضوئي تابعة لزاوية الاستقطاب بين الإشارة المستقبلة وإشارة الهزاز الليزري المحلي، ولتحقيق درجة عالية من الدقة في كشف الإشارة المفيدة فإن  يجب أن يكون مساوٍ للواحد. لذلك يجب التحكم بالاستقطاب. • للمضخمات تأثير سلبي على نسبة الإشارة إلى الضجيج (Signal to Noise Ratio, SNR) ، والهزازات الليزرية حلاً بديلاً. Our paper contains a study of the effects of polarization control and amplifiers on the performance of the coherent detection optical systems. It also offers a new definition of the block diagram of the coherent system. Mathematical analyses and simulation of coherent system show that: • coherent optical communication systems potentially offer improved receiver sensitivity and channel selectivity over direct-detection techniques. • the optical power incident on the photodetector is a function of the polarization misalignment  between the signal wave and local oscillator wave. To achieve a high degree of fidelity in the recovered signal, this term should remain constant and equal to one. Thus, polarization control is necessary. • the amplifiers have negative effects on the signal to noise ratio (SNR), thus, local laser oscillator is alternative solution.